2022
DOI: 10.3390/antiox11061119
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Acne Effects of Hamamelis virginiana Bark in Human Keratinocytes

Abstract: Cutibacterium acnes (C. acnes) is recognized as one of the main triggers of the cutaneous inflammatory response in acne vulgaris, a chronic skin disorder with a multifactorial origin. Witch hazel (Hamamelis virginiana L.) is a plant widely used for skin inflammatory conditions, with some preliminary anti-inflammatory evidence on the skin, but lacking data on acne conditions. This study aimed to evaluate the effect of a glycolic extract from Hamamelis virginiana bark (HVE) versus C. acnes-induced inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
(39 reference statements)
1
24
0
1
Order By: Relevance
“…We previously reported that the glycolic extract included in the present study (HVE) mainly contains HT (0.30%) and oligomeric proanthocyanidins (0.29%) [ 13 ]; however, pure HT (until 10 μM, roughly corresponding to 5 μg/mL) was not able to explain the inhibitory activity of HVE against C. acnes or TNF-α-induced inflammation in human keratinocytes, thus suggesting the importance of oligomeric proanthocyanidins.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…We previously reported that the glycolic extract included in the present study (HVE) mainly contains HT (0.30%) and oligomeric proanthocyanidins (0.29%) [ 13 ]; however, pure HT (until 10 μM, roughly corresponding to 5 μg/mL) was not able to explain the inhibitory activity of HVE against C. acnes or TNF-α-induced inflammation in human keratinocytes, thus suggesting the importance of oligomeric proanthocyanidins.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous research on the anti-inflammatory activity of HVE in HaCaT cells, we observed the promising inhibitory effects of hamamelis glycolic extract on several TNF-α-induced mediators [ 13 ]. Cytokines belonging to the IL-17 family are known to regulate epithelial barrier homeostasis during infections, but also to contribute in autoimmune processes, in which TNF-α plays a crucial role (for a review on the topic, refer to Pappu et al [ 30 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations